‘LONG TERM IMPACT OF INDUCED DISPLACEMENT AND RELOCATION ON ADOLESCENCE; WITH A FOCUS ON WELLANGIRIYA AREA, SRI LANKA' (Proceedings of the International Conference on Social Sciences, 2018)
All most all of the large scale development project create victims and beneficiaries in large number. Number of people are induce displace or involuntary displace from their houses due to such development projects. Improper planning in displacement and relocation can lead to both long-term and short-term negative consequences for the entire society. Every group in the induced displace community should be considered in relocating, one such group that should be focus on, is the adolescents of the displaced community. It is important to understand whether dramatic changes took place within environment surrounding them actually influence their lives.This study was conducted in Wellangiriya in Colombo District. During 1977 people who lived in slums and shanties in Narahenpitaarea were induced displaced because of large scale urban beautification and development project in Colombo area. Objective of the study was to understand how adolescents (during 1977) coped up with the induce displacement and relocation process, and understand how that influence to shaped up their current lifestyles. As for data collection both quantitative and qualitative data were gathered using different techniques such as, interview methods, questionnaires and focus group discussions.Study revealed that changes took place due to induced displacement and improper relocation influenced them as adolescents in various ways and as mid age people they still have to deal with results of relocation. Thus this study shows that unplanned displacement and relocation will create beneficiaries for sure but it might also create number of victims too.
Keywords: relocation; improper planning; adolescents; coping; livelihood; education